Quercetin, a Flavonoid Antioxidant, Ameliorated Procarbazine-Induced Oxidative Damage to Murine Tissues - Ebenezer Tunde Olayinka; Ayokanmi Ore; Oluwatobi Adewumi Adeyemo; Olaniyi Solomon Ola; Olaoluwa Oluwaseun Olotu; Roseline Chinonye Echebiri (MDPI AG, 2015)
Procarbazine (PCZ) (indicated in Hodgkin's disease), is an alkylating agent known to generate free radicals in vivo, while Quercetin (QCT) is a flavonoid antioxidant with proven free radical scavenging capacity. This study investigated the protective effects of QCT on PCZ-induced oxidative damage in the rat. Male Wistar rats (160-180 g) were randomized into five groups (n = 5/group): I (control), II PCZ-treated (2 mg/kg body weight (bw) for seven days); III pre-treated with QCT (20 mg/kg bw) for seven days, followed by PCZ for seven days; IV co-treated with PCZ and QCT for seven days and V administered QCT alone for seven days. PCZ caused a significant increase in plasma total bilirubin, urea, and creatinine when compared with control (P < 0.05). Similarly, plasma activities of alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and γ-glutamyl transferase (γ-GT) were significantly increased in the PCZ-treated group relative to control. Furthermore, PCZ caused a significant decrease in the activities of hepatic superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST) as well as levels of ascorbic acid (AA) and glutathione (GSH). This was followed by a significant increase in hepatic malondialdehyde (MDA) content. However, QCT pre-treatment and co-treatment ameliorated the PCZ-induced changes in plasma levels of urea, creatinine, and bilirubin as well as the activities of ALP, AST, ALT, and GGT. QCT also ameliorated hepatic AA and GSH levels and the activities of SOD, CAT, and GST. This all suggests that QCT protected against PCZ-induced oxidative damage in rats.